A Compartmental Model for Simulation of IGF-I Kinetics and Metabolism - Boroujerdi, M. A.; Sonksen, P. H.; Jones, R. H. (Methods of Information in Medicine, 1994)
A compartmental model for the simulation of in-vivo insulin-like growth factor one (IGF-I) kinetics and metabolism is presented. The model is based on the concept that IGF binding proteins (IGFBPs) act as a reservoir for IGF-I in plasma, thereby restricting its access to the extravascular space. The model is divided into two subsystems; a binding model for IGF-I and IGFBP, and an IGF-I clearance model, which includes the binding of IGF-I to IGF-I receptors. The non-linear differential equations describing the model are based on the law of mass action. Given the steady state condition, the linearized form of the model, describing tracer kinetics of IGF-I and IGFBPs is developed. It is demonstrated that using the available data, it is possible to assign values to the model parameters, thereby allowing simulation of the model to obtain information not accessible by direct observation.
Keywords: Compartmental Model; Simulation; Modelling; Pharmacokinetics